The impact of visual ergonomic control elements and learning methods on developing website design skills among educational technology students - Basuny, Abeer Bedair; Almutairi , Hakimah Saleh; Ibrahim , Sherif Ahmed; El-Okkiah, Amira Ahmed fouad Hassan; Elbradei, Ashraf Mohamed Mohamed (Research Journal in Advanced Humanities, 2025)
The main goal of a website's ergonomics is to meet the user's specific needs in the most efficient way, ensuring ease of interaction with the site's content. This includes making text easier to read, making information easier to find, and making actions easier, such as requesting a product or service, Therefore, the current study aimed to study the effect of visual ergonomic control elements and learning methods on developing website design skills among educational technology students, The sample consisted of 60 students in the Department of Educational Technology and Computers at the Faculty of Specific Education, Kafr Elsheikh University, in the e-learning course. The students were divided into four experimental groups of 15 students each, by classifying the students into two categories of learning methods (visual - auditory), and each category of learning methods. Previous learning is divided into two categories according to the use of (visual ergonomic control - traditional learning method) The results of the research found that students with a visual learning style and the use of ergonomic adjustment factors are more effective in enhancing students’ website design skills.